"I Want Different for My Child:" An Interpretative Phenomenological Analysis of Mothers' Histories of Disordered Eating and the Impact on Their Parenting Approach. (April 2023) - Horton, Emily
Prevalence rates of disordered eating behaviors impact 13% of young women and 7% of young men in the United States. Most existing research emphasizes the significant impact that the family of origin, namely parents, has on the children's relationship with food, their body, and exercise. Yet, little research exists on the parents' experience healing from disordered eating and its impact on their approach to parenting. Accordingly, this paper presents an in-depth exploration of the lived experiences and personal meaning of mothers' experience healing from disordered eating and its impact on their childrearing approach. Semistructured interviews were conducted and analyzed as per interpretative phenomenological analysis. Four themes emerged my upbringing and its impact on my relationship with my body, removing shame and changing my family tree, reparenting ourselves alongside our children, and it's bigger than food. The findings highlight the importance of supporting parents in their healing process specific to disordered eating as well as their parenting approach to change their family's relationships with food, bodies, and movement.